A SO2 flux study of the Etna volcano 2020–2021 paroxysmal sequences - Aiuppa, Alessandro; Lo Bue Trisciuzzi, Giovanni; Alparone, Salvatore; Bitetto, Marcello; Coltelli, Mauro; Delle Donne, Dario; Ganci, Gaetana; Pecora, Emilio (Frontiers in Earth Science, 2023)
The persistent open-vent degassing of Mt. Etna is often punctuated by months-long paroxysmal sequences characterized by episodes of violent strombolian to lava fountaining activity. Understanding these gas-fueled transitions from quiescence to eruption requires routine measurement of gas fluxes. Here, we report SO2 flux measurements, obtained from a permanent UV camera system, collected over a two-year-long period spanning two paroxysmal sequences of Etna’s New South East Crater (NSEC) in December 2020/April 2021 and May/October 2021. In both cases, SO2 flux increased from ≤ 3250 Mg/day during ‘ordinary’ activity to ≥ 4200 Mg/day. We interpret these distinct SO2 degassing regimes in light of seismic and thermal observations and drawing on numerical simulations of sulfur degassing constrained by parental melt sulfur contents in Etna’s hawaiites. We find that initiation of a paroxysmal sequence results from an approximate doubling of the time-averaged rate of magma supply (and degassing) above the sulfur exsolution level ( 150 MPa pressure), to >4 m3/s. This corroborates recent models that argue for the triggering of paroxysmal sequences by escalating supply of volatile-rich magma to a reservoir 3–4 km below the summit region. The non-stationary nature of magma flow and volcanic degassing we identify highlights the need for sustained surveillance to characterize long-term atmospheric budgets of volcanic volatiles.